Optimalisasi Pelaksanaan Pelayanan Hukum bagi Penyandang Disabilitas di Kejaksaan Tinggi Bali - Sudharma, Kadek Januarsa Adi; Shadrina, Salsabila Nur (Fakultas Hukum Universitas Semarang, 2024)
As a state governed by law, Indonesia has an obligation to provide protection and equal access to justice for all its citizens, including persons with disabilities. This report examines the efforts of the Bali High Prosecutor's Office in optimizing legal services for persons with disabilities, in accordance with Law Number 8 of 2016 concerning Persons with Disabilities. Through research using observation and interview methods, steps taken and challenges faced were identified. Although the Bali High Prosecutor's Office has made significant efforts based on Guideline Number 2 of 2023, challenges such as a lack of accessible infrastructure, limited legal understanding among persons with disabilities, and a shortage of trained human resources still exist. Therefore, further strategies are needed to ensure equal treatment for persons with disabilities before the law, including increasing training for law enforcement officials and improving more inclusive facilities. This journal is expected to serve as a guide for other institutions in developing more disability-friendly legal services.